Economic evaluation in child health - Ungar, Wendy J. (Oxford : Oxford University Press, 2010)
As the conduct of health economic evaluations to inform health budget decision-making becomes more common, the special challenges of measuring costs and health consequences in children, from neonate to adolescent, have become increasingly evident. This book considers these challenges.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Child health services -- Economic aspects; Pediatrics -- Economic aspects